Climate Policy Commitment and Green Metal Prices: Evidence from the Paris Agreement - Megha Patnaik (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2026)
Metal markets are an important but understudied aspect of the global energy transition. This paper demonstrates differential metal price responses to the Paris Agreement based on their role in the energy transition. We use a difference-in-differences design with daily price data from 2001 to 2024 for eight industrial metals. The treatment group distinguishes between traditional green metals (Copper, Aluminium, Nickel), which are established in renewable energy infrastructure, versus emerging green metals (Lithium), that are critical for storage. The control group includes non-green metals (Zinc, Lead, Tin, and Iron Ore). We find traditional green metals experienced 31% price decline relative to control metals following the Paris Agreement, while Lithium exhibited a 120% price increase.
Keywords: Q54; Q58; G14; L72; 330; Paris agreement; green transition; metal prices